Reflect on the importance of the national humanization policy in maternal and child care (Research, Society and Development, 2021)
Introduction: Humanization in health is one of the pillars for building dignified, fair and holistic care. Understanding and meeting all the needs of health users, as well as including and creating a bond between professionals and users, having the socio-family network as fundamental support, allows for more humanized, joint and welcoming care. Objective: to reflect on the importance of the National Humanization Policy (PNH) in maternal and child care. Methods: this is a reflective study based on a scientific theoretical basis, which is analytical-descriptive. Results: the construction of care is a process that requires the participation not only of the health professional, but also of users and the support of health management. The principles set out in the SUS (universality, equity and comprehensiveness) are essential for the provision of health services, however, there are gaps within the SUS that make it difficult to develop. Therefore, the NHP together with the PHPN and Rede Cegonha within maternal and child care, ensure and guarantee better assistance to users and their socio-family network and health workers, making assistance more human, dignified, welcoming, providing the right of all, in addition to providing a question between the patient and the professional, forming bonds between them. Conclusion: therefore, the PNH plays a great role, which is of great importance for the formation of a more humanized, dignified, welcoming health system, enabling improvements in the entire range of health care.